Food allergy in Singapore: opening a new chapter - Lee, Alison Joanne (Singapore Med J, 2014)
With the exception of shellfish, the overall food allergy rates in Singapore have not reached the epidemic proportions of the West. The rates of egg, milk and fish allergies remain low. However, the patterns of some food allergies in Singapore have changed over the last decade. For example, peanut allergy, once rare in Singapore, is now the most common cause of anaphylaxis in children. Studies analysing lifestyle practices, particularly with respect to prevention of food allergy, are necessary in order for practitioners to understand global differences and maintain this low prevalence.